An Investigation into Socio-Political Constraints on Decarbonization in Akwa Ibom State, Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigated socio-political constraints on decarbonization in Akwa Ibom State, Nigeria, with emphasis on how governance structures, institutional frameworks, political interests, and stakeholder dynamics influence policy implementation and outcomes. A descriptive survey research approach was used in the research, covering three oil-producing Local Government Areas (LGAs) in the state: Eket, Ibeno and Eastern Obolo. The primary data for the study were obtained using structured questionnaires distributed to a sample of 400 respondents selected using a multistage sampling procedure, while field observations were also used. Descriptive statistics, Pearson Product-Moment Correlation (PPMC) and multiple regression analyses were used for analysing the data collected from the field at a 0.05 level of significance. From the analysis, it was found that socio-political elements such as political interest in oil revenues, socio-political instability, and economic dependency on fossil fuels significantly hinder decarbonization processes. Perceived lack of effectiveness of government stakeholders, community stakeholders, and industry stakeholders in the push for decarbonization was established through stakeholder analysis, while it is agreed upon that there is a need for collaboration and awareness for better results. Also, the respondents highlighted the poor progress in the realisation of decarbonization outcomes, such as low levels of reductions in carbon emissions, inadequate use of renewable energy and continued deterioration of the environment. Inferential statistics revealed a statistically significant correlation between socio-political factors and the implementation of decarbonization policies (r = 0.808; p < 0.05), between governance and institutional factors and decarbonization activities (F = 97.609; p < 0.05) and finally between stakeholder roles/perceptions and decarbonization outcomes (r = 0.833; p < 0.05). The regression analysis shows that stakeholder perceptions/roles accounted for 39.7% of the variability in decarbonization outcomes. In conclusion, decarbonization activities in Akwa Ibom State are greatly hampered by the prevailing socio-political factors, institutional weaknesses and ineffective stakeholder involvement in achieving poor environmental transition outcomes.